Th1/Th17 polarization persists following whole-cell pertussis vaccination despite repeated acellular boosters - da Silva Antunes, R; Babor, M; Carpenter, C; Khalil, N; Cortese, M; Mentzer, A; Seumois, G; Petro, C; Purcell, L; Vijayanand, P; Crotty, S; Pulendran, B; et al. (American Society for Clinical Investigation, 2018)
In the mid-1990s, whole-cell (wP) pertussis vaccines were associated with local and systemic adverse events, which prompted their replacement with acellular (aP) vaccines in many high-income countries. In the past decade rates of pertussis disease have increased in children receiving only acellular pertussis vaccines. We compared the immune responses to acellular pertussis boosters in children who received their initial doses with either wP or aP vaccines using activation-induced marker (AIM) assays. Specifically, we examined pertussis-specific memory CD4+ T cell responses ex vivo, highlighting a Type 2/Th2 versus Type 1/Th1 and Th17 differential polarization as a function of childhood vaccination. Remarkably, after a contemporary aP booster, cells from donors originally primed with aP were 1) associated with increased IL-4, IL-5, IL-13, IL-9 and TGF-β and decreased IFNγ and IL-17 production;2) defective in their ex vivo capacity to expand memory cells; and 3) less capable to proliferate in vitro. These differences appeared to be T cell-specific, since equivalent increases of antibody titers and plasmablasts after aP boost were seen in both groups. In conclusion, our data suggest that long lasting effects and differential polarization and proliferation exists between adults originally vaccinated with aP versus wP despite repeated acellular boosters.